Rancang Bangun Instrumen Pengukur Tinggi Gelombang Permukaan Laut Menggunakan Sensor IMU GY955 - Widyo Astomo, Reynanda Bagus; Kurniawati , Indah; Mahmudah , Aida; Sya’ronni (Program Studi Teknik Elektro - Fakultas Teknik - Universitas Widyagama Malang, 2023)
Ocean waves are an up and down movement of sea water that occurs due to several factors such as wind, sun and moon gravity, volcanic eruptions or earthquakes at sea, moving ships, and so on. Information about the structure of sea water waves off the coast is very useful for human activities related to the sea such as fishing, shipping, and other activities. Based on this, it is necessary to have a tool that can monitor the height of the tides and low tides. The purpose of making this device is to determine the characteristics of sea water waves directly (real time) in order to determine the right time to sail off it was found that there is a difference in the maximum wave height reading of ±8 cm and an average difference of ±5 cm. While the difference in readings of wave crests has a maximum difference of ±7 cm and an average difference of ±4 cm.